2023
DOI: 10.3390/cells12182215
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and Regulation of Canonical Transient Receptor Potential 3 (TRPC3) Channels

Bethan A. Cole,
Esther B. E. Becker

Abstract: Canonical transient receptor potential 3 (TRPC3) channel is a non-selective cation permeable channel that plays an essential role in calcium signalling. TRPC3 is highly expressed in the brain and also found in endocrine tissues and smooth muscle cells. The channel is activated directly by binding of diacylglycerol downstream of G-protein coupled receptor activation. In addition, TRPC3 is regulated by endogenous factors including Ca2+ ions, other endogenous lipids, and interacting proteins. The molecular and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Thus, we identified more than one molecular correlate of heterogeneity across lobules, within known components of mGluR-TRPC3 signaling pathways. In addition, these signaling components are likely to interact with each other (Cole and Becker, 2023). Moreover, our bioinformatic analysis by separating cells from different lobules obscures the within-lobule heterogeneity observed both in previous studies of the Purkinje cell transcriptome and in our data (Kozareva et al, 2021).…”
Section: Heterogeneity In Mglur1-trpc3 Signaling May Contribute To Pu...mentioning
confidence: 54%
See 4 more Smart Citations
“…Thus, we identified more than one molecular correlate of heterogeneity across lobules, within known components of mGluR-TRPC3 signaling pathways. In addition, these signaling components are likely to interact with each other (Cole and Becker, 2023). Moreover, our bioinformatic analysis by separating cells from different lobules obscures the within-lobule heterogeneity observed both in previous studies of the Purkinje cell transcriptome and in our data (Kozareva et al, 2021).…”
Section: Heterogeneity In Mglur1-trpc3 Signaling May Contribute To Pu...mentioning
confidence: 54%
“…However, we found that the non-competitive mGluR1 antagonist CPCCOEt (Hartmann et al, 2008) blocked slow EPSCs in all three regions (Figure S4a), arguing against this possibility. Downstream of mGluR1, the slow EPSC is mediated by the nonselective cation channel TRPC3 (Hartmann et Cole and Becker, 2023), which both partially block the slow EPSC, allowing us to measure the kinetics of the remaining current. We found that the magnitude of the slow EPSC was consistently reduced by genistein and by SKF96365 across lobules, but there was no shift in timing that could explain the differences between lobules (Figure S4b-e).…”
Section: Heterogeneity In Mglur1-trpc3 Signaling May Contribute To Pu...mentioning
confidence: 99%
See 3 more Smart Citations